PENERAPAN PEMETAAN GAGASAN (CONCEPT MAPPING) DALAM MANAJEMEN MUTU DI LABORATORIUM KLINIK - H Kahar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Quality laboratory services are always been monitored in order to improve the quality deficiencies. Some quality concepts have beenimplemented in laboratory quality assurance; concept mapping might be implemented as one of the choices. Concept mapping has oftenbeen implemented in various organizations such as in the clinical laboratory.